Neuroprotective Effects of a Smoothened Receptor Agonist against Early Brain Injury after Experimental Subarachnoid Hemorrhage in Rats - Hu, Quan; Li, Tong; Wang, Lingxiao; Xie, Yunkai; Liu, Song; Bai, Xuemei; Zhang, Tiantian; Bo, Shishi; Xin, Danqing; Xue, Hao; Li, Gang; Wang, Zhen (Frontiers in Cellular Neuroscience, 2017)
The sonic hedgehog (Shh) signaling pathway plays a fundamental role in the central nervous system development, but its effects on neural cell survival and brain repair after subarachnoid hemorrhage (SAH) has not been well investigated. The present study was undertaken to evaluate the influence of an agonist of the Shh co-receptor Smoothened (Smo), purmorphamine (PUR), on early brain injury as well as the underlying mechanisms after SAH. PUR was administered via an intraperitoneal injection with a dose of 0.5, 1 and 5 mg/kg at 2h, 6h, 24h and 46h after SAH in rat model. The results showed that PUR treatment significantly ameliorated brain edema, improved neurobehavioral function and attenuated neuronal cell death in the prefrontal cortex (PFC), associated with a decrease in Bax/Bcl-2 ratio and suppression of caspase-3 activation at 48h after SAH. PUR also promoted phospho-ERK levels. Additionally, PUR treatment markedly decreased MDA concentration accompanied with the elevation in the expression of nuclear factor erythroid 2-related factor 2 and heme oxygenase-1in PFC. Notably, PUR treatment significantly reversed the changes of Shh pathway mediators containing Patched, Gli1, and Shh by SAH insult, and the neuroprotection of PUR on SAH was blocked by Smo antagonist cyclopamine. These results indicated that PUR exerts neuroprotection against SAH-evoked injury in rats, mediated in part by anti-apoptotic and anti-oxidant mechanism, up-regulating phospho-ERK levels, mediating Shh signaling molecules in the PFC.